Minimal social exclusion: a means to increased information gain in human intelligence interviews, 2016-2017 - Ask, Karl (UK Data Service, 2021)
Eliciting information from semicooperative sources presents a major challenge in investigative and intelligence settings. This research examines the role of the human need to belong in individuals' willingness to disclose critical information. We hypothesised that social exclusion would exert a threat to individuals' need to belong and self‐esteem, which would make them strive for social reconnection through sharing information with others. In two experiments (N = 150 and N = 135), social exclusion and inclusion were manipulated before participants were given the opportunity to disclose critical information in a semicooperative game setting (Study 1) or a mock intelligence interview (Study 2). Social exclusion did not influence information disclosure in any of the experiments. Instead, however, social inclusion unexpectedly increased information disclosure in the interview setting. We conclude that prior social experiences can influence the outcome of subsequent interviews, but the precise mechanisms underlying such influence are currently unknown. The following article has been published on these data: Ask, K., Ejelöv, E., & Granhag, P. A. (2019). Eliciting human intelligence: The effects of social exclusion and inclusion on information disclosure. Journal of Investigative Psychology and Offender Profiling, 16(1), 3–17. https://doi.org/10.1002/jip.1516. The proposed research concerns how to effectively establish rapport and increase human-intelligence sources’ willingness to share reliable information with law enforcement and security/intelligence agencies. Gaining sources’ cooperation using ethically defensible methods is a major challenge, and has only recently received researchers’ attention. The current project will add to this burgeoning strand of research by proposing and evaluating a novel intervention with a solid foundation in social psychological theory. Based on the scientific literature on ostracism, we predict that experiencing a brief episode of minimal social exclusion (e.g., being ignored in a conversation) immediately before entering an interview will increase a source’s willingness to share information with the interviewer. Extensive research has shown that such minimal manipulations, under the right circumstances, cause large and reliable increases in prosocial behaviors (e.g., nonconscious mimicry, money donations, eagerness to work with others). The effect of social exclusion on information sharing, however, has not been studied to date. The reason why even minimal signs of social exclusion have such large influence on human behavior is that ostracism threatens four very fundamental human needs (belonging, self-esteem, control, and recognition/meaningful existence). When such threats are detected, an individual will feel, think, and act in ways that serve to restore optimal levels of the threatened needs. Depending on the context and which need is most saliently threatened, the individual may act more prosocially (to restore belonging and self-esteem) or more aggressively (to restore control and recognition) toward others. Fortunately, the conditions that determine the likely behavioral response are well understood. Hence, it is possible to construct an interview setting that maximizes the opportunity for prosocial information sharing. In this project, we will examine the ostracism intervention in two experiments. In Experiment 1, participants will engage in a computer-based setup which is conceptually analog to information-management dilemmas that sources face in real-life intelligence scenarios. In Experiment 2, participants will engage in a more realistic, immersive setup, where they role-play being linked to a planned terrorist attack. Ostracism will be manipulated using staged social exclusion/inclusion in a computer game (Experiment 1) or in live interaction with confederates posing as fellow participants (Experiment 2); both procedures are standard in the ostracism literature. We predict that social exclusion will increase participants’ proclivity to share hidden information with new interaction partners (i.e., interviewers) following the ostracism manipulation. The research has potential for substantial impact, both academically and practically. Academically, the findings would contribute to the literature on intelligence interviewing and pave the way for further theory-driven research on the topic. Due to the use of information sharing as a novel outcome measure in ostracism research, the findings should also interest a more general audience of scholars in social psychology. Practically, the ostracism intervention (should it receive empirical support) is reasonably easy to implement in intelligence-gathering settings, and can readily be communicated to stakeholders and incorporated in existing training programs. Active collaboration with the user community is a key component of the project, which will maximize the relevance and utility of the conducted research.